Pedagogical Transformation Models in Schools in Nepal during the Global Pandemic (Journal of School Administration Research and Development, 2020)
This essay reviews the emergency teaching-learning pedagogy in K-12 schools of Nepal during the COVID-19 global pandemic. It discusses three models (unidirectional, e-participatory, and mobile teaching) as alternative pedagogies of Nepalese educational institutions to continue teaching-learning for different disciplines such as language, arts, and social studies. Moreover, the essay discusses the appropriateness of each model for teaching-learning in urban, semi-urban, and rural settings in Nepal.